2015
DOI: 10.19030/jabr.v31i4.9336
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study Of Factors Influencing Organisational Justice Among Government Employees

Abstract: Organisational justice has become prominent within the leadership literature as an underlying and important aspect of governance. This study set out to examine factors influencing employees organisational justice perceptions in a South African government department. The perceptions of the 289 participants were investigated by using the Organisational Justice Measurement Instrument (OJMI) as a measure of organisational justice. Descriptive statistics of the sample and factor analysis were conducted to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In terms of company scale and type of job done, the firms in the study are almost equal. According to Ledimo (2015), every company is undersized, containing 3 to 17 workers, hence every employee participates in the procedure relating to designing novel and/or upgraded goods. There are two explanations why such a sample was selected.…”
Section: Methodology Study Sample Selectionmentioning
confidence: 99%
“…In terms of company scale and type of job done, the firms in the study are almost equal. According to Ledimo (2015), every company is undersized, containing 3 to 17 workers, hence every employee participates in the procedure relating to designing novel and/or upgraded goods. There are two explanations why such a sample was selected.…”
Section: Methodology Study Sample Selectionmentioning
confidence: 99%
“… Cohen-Charash and Spector (2001) highlight that in original studies of organisational justice, perceived distributive injustice was found to have a negative impact on the cognitive and emotional state of employees, resulting in decreased workplace attendance and performance. Second, procedural justice, which refers to the organisational processes and procedures through which outcomes are realised, but not necessarily to the outcomes themselves, even though they may be individually unfavourable: the notion that the fairness of the procedure leading to the outcome is more important than the outcome itself ( Ledimo, 2015 ). In instances of perceived procedural injustice, rather than the unfairness manifesting itself in individual dismay, the resulting negativity and sense of injustice is directed towards the organisation ( Cohen-Charash and Spector, 2001 ).…”
Section: A Climate Of Organisational Justicementioning
confidence: 99%
“…Other studies investigated emotion, such, Ledimo (2015) proposed that procedural and interactional justice are interactiong in predicting individual's emotion. Emotion is mediating the relationship between perceieved organizational justice and revenge act.…”
Section: Organizational Justice and Emotionmentioning
confidence: 99%